2019
DOI: 10.3390/hydrology6030072
|View full text |Cite
|
Sign up to set email alerts
|

Mid-Century Climate Change Impacts on Ouémé River Discharge at Bonou Outlet (Benin)

Abstract: This work focuses on impacts of climate change on Ouémé River discharge at Bonou outlet based on four global climate models (GCM) over Ouémé catchment from 1971 to 2050. Empirical quantile mapping method is used for bias correction of GCM. Furthermore, twenty-five rain gauges were selected among which are three synoptic stations. The semi-distributed model HEC-HMS (Hydrologic Modeling System from Hydrologic Engineering Center) is used to simulate runoff. As results, HEC-HMS showed ability to simulate runoff wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 41 publications
(64 reference statements)
0
12
0
Order By: Relevance
“…This reconstructed time series shows that over the study period, the maximum river discharge was of Q riv 1100 m 3 /s in November 2019. Such high values of river flux have been obtained from models of the Ouémé watershed (Lawin et al, 2019). Unsurprisingly, there is a strong annual variability and much more water has been drained into the lagoon in the wet season of 2019 than in 2018.…”
Section: Estimate Of Parametersmentioning
confidence: 85%
See 1 more Smart Citation
“…This reconstructed time series shows that over the study period, the maximum river discharge was of Q riv 1100 m 3 /s in November 2019. Such high values of river flux have been obtained from models of the Ouémé watershed (Lawin et al, 2019). Unsurprisingly, there is a strong annual variability and much more water has been drained into the lagoon in the wet season of 2019 than in 2018.…”
Section: Estimate Of Parametersmentioning
confidence: 85%
“…Although the net river flow considerably varies from the dry to the wet season, an exact quantification remains uncertain as rivers are not regularly gauged. Previous studies report river flow variations from a few tens of m 3 /s in the dry season to 1000 m 3 /s in the wet season (Chaigneau et al, 2022;Le Barbé et al, 1993;Djihouessi and Aina, 2018;Lawin et al, 2019). This strong seasonal variation of freshwater inflow results in a complete seasonal reversal of the salinity and ecosystem of the lagoon (Lalèyè et al, 2003;Okpeitcha et al, 2022) and can lead to major floodings.…”
Section: Introductionmentioning
confidence: 95%
“…This latter region is characterized by a single rainy season, with maximum precipitation between July and October (Biao, 2017;Ahokpossi, 2018;Lawin et al, 2019, Colleuil, 1987. The maximum discharge into the lagoon between September and November is unknown (rivers ungauged in the coastal region) and varies, depending on authors, from ~400 m 3 s -1 (Le Barbé et al, 1993;Djihouessi and Aina, 2018) to more than 1000 m 3 s -1 (Lawin et al, 2019). This river discharge produces a complete desalinization of the Nokoué Lagoon and a strong increase of its volume (Texier et al, 1980;Colleuil, 1987;Djihouessi and Aina, 2018).…”
Section: Study Area and Hydrologymentioning
confidence: 99%
“…During the short rainy season of South Benin, which coincides with the rainy season in North Benin, the Ouémé and Sô rivers are in flood and discharge a large amount of fresh water into Nokoué lagoon (Gadel and Texier, 1986;Djihouessi and Aina, 2018). The maximum discharge into the lagoon between September and November is badly known (rivers not regularly gauged in the coastal region), but some studies reported maximum river fluxes varying, depending on authors, from ~400 m 3 s -1 (Le Barbé et al, 1993;Djihouessi and Aina, 2018) to more than 1000 m 3 s -1 (Lawin et al, 2019). The mean water level in the lagoon, which is of ~1.3 m in dry season (Figure 1c), increases by up to ~90 cm during river floods to reach an average value of ~2.20 m (Chaigneau et al, 2021).…”
Section: Introductionmentioning
confidence: 99%